Effect of Leaflet-Based Education on Knowledge and Exclusive Breastfeeding Compliance Among Mothers in North Sumatera - Maidah Maidah; Ingka Kristina Pangaribuan; Retno Wahyuni; Erin Padilla Siregar; Lisa Erawati Sibarani (Health Dynamics, 2025)
Background: Exclusive breastfeeding is the practice of providing only breast milk without any additional food or drink for the first six months of an infant’s life. The coverage of exclusive breastfeeding in Indonesia has not yet reached the target, partly due to the low level of knowledge and compliance among breastfeeding mothers. One effort to improve this condition is through health education using leaflet media. This study aimed to determine the effect of leaflet media on the knowledge and compliance of breastfeeding mothers in providing exclusive breastfeeding at Ulumahuam Public Health Center, South Labuhan Batu Regency, in 2025. Methods: This research used a quasi-experimental design with a one-group pretest-posttest approach. The population consisted of 72 breastfeeding mothers, with a sample of 42 respondents selected using a simple random sampling technique. Data were collected using questionnaires and analyzed using the paired t-test and chi-square test. Results: The results showed a significant increase in mothers' knowledge after they were given education through leaflet media, with a p-value = 0.000 (<0.05). In addition, there was a significant effect of leaflet media on mothers' compliance in providing exclusive breastfeeding, with a p-value = 0.002 (<0.05). This indicates that leaflet media is effective in improving knowledge and compliance among breastfeeding mothers. Conclusion: Leaflet media has a significant effect on increasing the knowledge and compliance of mothers in providing exclusive breastfeeding. It is recommended that health workers utilize leaflet media as an educational tool in promoting exclusive breastfeeding programs.